Pengaruh Orientasi Pembelajaran, Kemampuan Produksi, dan Orientasi Pasar Terhadap Strategi Bisnis dan Kinerja Bisnis - J.E. Sutanto (KINERJA, 2009)
One indicator of company’s or business’s successfulness in the competition was the company or business must have competitive advantage that allowed the industrial company of foods and beverages yielding the superiority of production result than their competitors in the determining the strategy and business performance continually.  The population of this research was foods and  beverages  industry  especially  big  and  medium  industrial company,  which  have  multi-business  and  multi-products  in  the  East  Java area  that  consist  of  1286  industrial  companies of  foods  and  beverages according  to  the  Indonesian  Business  Field  Classification    (KLUI  15) years 2002.  The  data  analysis  technique  used  Structural  Equation  Modeling  = SEM)  with computer  help  used  AMOS  program  4.0  version.The  research result  indicated  that:  (1)  all  of independent variables have positive influence and significant toward the business strategy and the business performance; (2) simultaneously the influence of teaching orientation, production competence  and  market  orientation  toward  business  strategy and  business  performance  was proper as the created model.  The conclusion of this research was the research result generally indicated  the  existence of positive  influence  that  experienced  by  that  industrial  company  of foods and beverages both from test result partially or simultaneously. And that not all of partial or simultaneous influence toward business strategy and business performance has positive or negative result, but it still categorized as reasonable.